Practice of junk food consumption among college students: an observational study in Northern Karnataka - T., Kavimalar; Gudadinni , Muttappa R. (International Journal Of Community Medicine And Public Health, 2023)
Background: Globalisation and urbanisation have significantly changed peoples eating patterns and forced many individuals to eat foods which have high calorie and low nutritional value foods called junk foods. Excessive consumption of fast food is often associated with increased risk of non-communicable diseases, presenting a public health challenge. India’s fast-food industry is expanding at the rate of 40% every year. India ranks 10th in the Fast-food per capita spending figures with 2.1% of expenditure in annual total spending. The aim of the study was to assess the knowledge and practice of junk food among college students. Methods: A cross sectional study was conducted among college students in Vijayapura city, during June to July 2022. The data was collected using semi-structured questionnaire, convenience sampling of 683 students were the participants of the study. Results: Out of 683 participants, 25.9% doesn’t care about the harmful effects of consuming junk. Around 61.8% of respondents are influenced by the taste and flavour of the junk. And 64.9 % of the respondents were aware enough to check mostly, whereas 29.3 percent were never had the habit of checking the nutrient fact label. Conclusions: As majority of the students consume junk, the adequate knowledge about the junk among them were relatively low, along with public health awareness, nutritional counselling can also be given to the students. And they are influenced mostly by the taste and easy availability.